2019
DOI: 10.3390/en12050775
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid-Powered Dual-Fluid Photovoltaic/Thermal (PV/T) System: Comparative Numerical Study

Abstract: A limited number of studies have examined the effect of dual-fluid heat exchangers used for the cooling of photovoltaic (PV) cells. The current study suggests an explicit dynamic model for a dual-fluid photovoltaic/thermal (PV/T) system that uses nanofluid and air simultaneously. Mathematical modeling and a CFD simulation were performed using MATLAB® and ANSYS FLUENT® software, respectively. An experimental validation of the numerical models was performed using the results from the published study. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…To enlarge the spectrum of the investigation, we decided to evaluate the environmental impact of barocaloric technology while the system mounts advanced HTF: The nanofluids [39][40][41][42][43][44][45]. Specifically, we tested variable concentrations of Al 2 O 3 -water nanofluids and of Cu-50%EG/50%W nanofluids, respectively, for heat-pumping and for cooling usages.…”
Section: Auxiliary Fluidsmentioning
confidence: 99%
“…To enlarge the spectrum of the investigation, we decided to evaluate the environmental impact of barocaloric technology while the system mounts advanced HTF: The nanofluids [39][40][41][42][43][44][45]. Specifically, we tested variable concentrations of Al 2 O 3 -water nanofluids and of Cu-50%EG/50%W nanofluids, respectively, for heat-pumping and for cooling usages.…”
Section: Auxiliary Fluidsmentioning
confidence: 99%
“…The number of hidden neurons can be identified by employing a trial-and-error procedure [57,58] or using some empirical rules, as reported in [59]. There is no specific process to evaluate the optimal number of hidden neurons, but it must be identified case by case.…”
Section: Training the Artificial Neural Networkmentioning
confidence: 99%
“…In this study the evaluation of the number of hidden neurons was made by employing an iterative trial-and-error process. The minimum number of hidden neurons N h,min was identified using the following empirical rule [59,60]:…”
Section: Training the Artificial Neural Networkmentioning
confidence: 99%
“…It has been extensively reported that nanofluids and working fluid mixed with nanoparticles possess superior thermal conductivity to that of pure fluid [5][6][7][8][9][10][11]. In particular, nanofluids have been applied in energy storage systems to enhance the thermal conductivity of the energy storage materials [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%